1972
DOI: 10.1139/z72-108
|View full text |Cite
|
Sign up to set email alerts
|

The response of Simulium (Eusimulium) euryadminiculum Davies (Diptera: Simuliidae) to some olfactory and visual stimuli

Abstract: The response of Simulium euryadminiculum Davies towards silhouettes of different shapes and colors was observed, using an ether extract of the uropygial gland of the common loon to concentrate the flies in the experimental locality and "Tanglefoot" to trap the flies on the silhouettes. These simuliids were attracted primarily to the head–neck portion of duck decoys, most flies landing on the leeward side. The simuliids were attracted to the terminal (and most prominent) portions of artificial head–neck or cyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Moreover, although a particular cue could attract insects, the combination of several derived stimuli could be more attractive to insects. Supporting this possibility, the ornithophilic Simulium euryadminiculum, which is highly attracted to extracts from uropygial glands (Fallis and Smith 1964), showed higher responses in the presence of both carbon dioxide and avian extracts than one stimulus alone, indicating a synergistic effect (Bennett et al 1972). Moreover, Allan et al (2006) found stronger mosquito attraction by the combined use of feathers and carbon dioxide than by using each component alone, although the strongest responses were obtained in the presence of a Leghorn hen.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, although a particular cue could attract insects, the combination of several derived stimuli could be more attractive to insects. Supporting this possibility, the ornithophilic Simulium euryadminiculum, which is highly attracted to extracts from uropygial glands (Fallis and Smith 1964), showed higher responses in the presence of both carbon dioxide and avian extracts than one stimulus alone, indicating a synergistic effect (Bennett et al 1972). Moreover, Allan et al (2006) found stronger mosquito attraction by the combined use of feathers and carbon dioxide than by using each component alone, although the strongest responses were obtained in the presence of a Leghorn hen.…”
Section: Discussionmentioning
confidence: 91%
“…Some black fly and mosquito species are attracted to secretions from the uropygial gland (Bennett et al 1972;Russell and Hunter 2005). However, in the case of Lutzomyia longipalpis, for example, a species commonly found in the field congregating around chicken coops, uropygial gland extracts did not increase insect captures (Nigam and Ward 1991).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Conversely, blood-seeking females of Simulium venustum Say land more frequently on dark purple, dark blue, and dark red, and least on dark green and yellow surfaces (Davies 1951(Davies , 1961(Davies , 1972. Females of S. euryadminiculum Davies, attracted by loon odor, similarly land least on yellow and green threedimensional objects (Bennett et al 1972). Such a shift in color preference in relation to behavioral state was noted also in Pieris brassicae (L.), the cabbage butterfly (Ilse 1928(Ilse , 1937.…”
Section: Introductionmentioning
confidence: 82%
“…Other reasons for certain areas of the body being preferred for biting may also relate to avoiding competition with other black fly or biting fly species. In ornithophilic species such as S. euryadminiculum and S. rugglesi, preferred biting sites are on the head and neck Bennett et al (1972) again presumably because the animal is less able to defend itself from flies in such places.…”
Section: Visual Interactions With Hostsmentioning
confidence: 99%